The effect of mulching materials on yield, biochemical composition and preservation of fruits of bell pepper - E. V. Yanchenko; D. I. Engalychev; N. A. Engalycheva; K. L. Alekseeva (Овощи России, 2022)
Introduction. The use of new covering materials is an important modern agrotechnique for cultivating of bell pepper in the open ground, which allows to minimize chemical treatments, increasing the yield, quality and preservation quality of vegetable products.The purpose of this work is to study the effect of various mulching materials (black polyethylene film and spandbond «Agrotex 60 perforated mulch») on the yield of bell pepper and also on biochemical composition of fruits and on their preservation quality in relation to the ripeness phase.Methods. The objects of the study were the fruits of two bell pepper hybrids of domestic and foreign breeding (respectively Nathalie F1 and Anetta F1), grown in the open ground using mulching materials. The experiments were laid according to standard methods adopted in vegetable growing. Storage was carried out in accordance with the methodological guidelines for conducting research on the storage of vegetables.Results. The use of mulching materials contributed to an increase in total yield and the yield of standard products in the crop structure, and also positively affected the accumulation of solids, vitamin C, monosaccharides, disaccharides and as a whole – the sum of sugars. The domestic hybrid Natalie F1 (74.9%), grown using black film as a mulching material, as compared to foreign hybrid Anetta F1 (71.3%), was characterized by better preservation quality. Significant differences in the chemical composition of fruits depending on the ripeness phase were revealed. Fruits laid for storage in full biological ripeness (red) were characterized by an increased amount of weight loss on all storage options. A positive effect on the storage persistence of bell pepper fruits with use of mulching materials on all variants of the experiment was also established.